A statistical comparison of the optical/UV and X-ray GRB afterglows observed using the Swift UVOT and XRT - Oates, S.; Page, M.; Schady, P.; de Pasquale, M.; Evans, P.; Page, K.; Chester, M.; Curran, Peter; Koch, T.; Kuin, N.; Roming, P.; Siegel, M.; et al. (2011)
In these proceedings we present a systematic and statistical comparison of 26 well sampled optical/UV light curves with their X-ray counterparts. We use three statistical methods to compare their behaviour and to determine the average properties of the sample and the properties of the individual GRBs. We show that the X-ray and optical/UV light curves are remarkably different during the first 500s after the BAT trigger, while they become more similar during the middle phase of the afterglow, i.e. between 2000s and 20000s. From 500s onwards, we find that the average properties of the optical/UV and X-ray light curves are consistent with the forward-shock model assuming a constant density external medium. However, the properties of the individual GRBs indicate that some of the individual afterglows are more complex and require different or additional assumptions, such as the presence of energy injection. We also discuss the implications of a number of GRBs in our sample having chromatic breaks and whether these breaks can be accommodated by the forward-shock model.